2017
DOI: 10.1002/ange.201704378
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Substituted Pyridines through Copper‐Catalyzed Condensation of Oximes and α,β‐Unsaturated Imines

Abstract: A copper‐catalyzed condensation reaction of oxime acetates and α,β‐unsaturated ketimines to give pyridine derivatives is reported. The reaction features mild conditions, high functional‐group compatibility, and high regioselectivity with respect to unsymmetrical oxime acetates, thus allowing the preparation of a wide range of polysubstituted pyridines, many of which are not readily accessible by conventional condensation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Initially, the excited photocatalyst species Ir(III)* ( E 1/2 (Ir(III)*/Ir(IV))=−1.73 V vs SCE) [21] enables a single‐electron transfer (SET) reduction of 1 a ( E red ( 1 a / 1 a⋅ − )=−1.78 V vs SCE) (see the Supporting Information for details) to deliver iminyl radical A , [4f,g,5,22] which couples with Cu(I) to give Cu(II) intermediate B . The isomerization of B affords Cu(II) species C [8b,9c,13f,18a,b,i] . Nucleophilic addition of C to imine 2 a leads to Cu(II)‐coordinated intermediate D [8b,18b,i] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the excited photocatalyst species Ir(III)* ( E 1/2 (Ir(III)*/Ir(IV))=−1.73 V vs SCE) [21] enables a single‐electron transfer (SET) reduction of 1 a ( E red ( 1 a / 1 a⋅ − )=−1.78 V vs SCE) (see the Supporting Information for details) to deliver iminyl radical A , [4f,g,5,22] which couples with Cu(I) to give Cu(II) intermediate B . The isomerization of B affords Cu(II) species C [8b,9c,13f,18a,b,i] . Nucleophilic addition of C to imine 2 a leads to Cu(II)‐coordinated intermediate D [8b,18b,i] .…”
Section: Methodsmentioning
confidence: 99%
“…The isomerization of B affords Cu(II) species C [8b,9c,13f,18a,b,i] . Nucleophilic addition of C to imine 2 a leads to Cu(II)‐coordinated intermediate D [8b,18b,i] . The protodemetalation of D affords a secondary amine‐tethered imine E , [18i] which tautomerizes to enamine F .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 More recently, Yoshikai et al reported a coppercatalyzed condensation of oximes and α,β-unsaturated ketimines to afford such pyridines (Scheme 1d). 14 However, the above reactions suffer from one or more drawbacks, such as multistep preparation of starting materials, expensive catalysts, and harsh reaction conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, symmetrically substituted (2,4,6–triaryl) pyridines are important because of their excellent material and biological profiles . The earlier syntheses of 2,4,6–triaryl pyridines involve a reaction between an aldehyde, methyl ketone, and a source of nitrogen . The synthesis of 2,4,6‐triaryl pyridines Yoshikai et al.…”
Section: Introductionmentioning
confidence: 99%